The Influence of Social Media Marketing on Wardah's Product Buying Interest mediated by Customer Trust - Azan Rahmat Muhammad; Teguh Widodo (PT Mattawang Mediatama Solution, 2023)
The study of the use of social media in the business world is becoming an increasingly attractive theme for business people and academics because the platform has the potential to increase business success. This study aims to investigate the effect of marketing activities that utilize social media features on interest in buying cosmetic products. This influence is thought to be mediated by the level of customer trust. A structural equation model (SEM) is established to examine the causal connection between the three variables. This model consists of four hypotheses, which will be tested using a sample of 200 quantitative data. The ordinal data was obtained from Wardah respondents who were asked to take part in an online survey by selecting 5 perception scales from 19 question items. After the survey data is declared valid and reliable and meets the Goodness of Fit requirements, the hypothesis is tested using the T-test criteria. The PLS software used to carry out all of these tests informs that all hypotheses are accepted, namely that Social Media Marketing activities have a positive and significant effect on Purchase Intention, both directly and indirectly, namely through Customer Trust. This significant indirect effect means that Social Media has a positive and significant effect on Customer Trust, and Customer Trust has a positive and significant effect on Purchase Intention. In other words, Customer Trust significantly mediates the influence of Social Media on Purchase Intention.